Investigation of the electrical resistivity structure of the subsurface at Mogod valley in central Mongolia: Insight is using 1D Magnetotelluric inversion - Enkhzul, Bayartogtokh; Batmagnai, Erdenechimeg; Tserendug, Shoovdor; Bayanjargal, Gendenpuntsag (Mongolian Geoscientist, 2022)
In this paper, we report a preliminary result of the Magnetotelluric investigation of the Mogod area. The Mogod region is one of the most prominent fields for geophysical study since the region includes young and active faults and geothermal activities. We conducted magnetotelluric measurements at 20 sites during geophysical field seasons in 2018-2021 as a pilot survey to understand data property and the electromagnetic noise level for the detailed electromagnetic studies. During the fieldwork, we used Lemi Magnetotelluric instruments and measured all three orthogonal components of the magnetic field and the horizontal components of the electric field. For the data processing, we used Matlab code by using the M-estimate regression method, and estimated the magnetotelluric transfer function with a lownoise level. The electrical resistivity model of the subsurface of survey layout shows us the existing resistivity anomalies at shallow-depth, and thickness of the upper crust approximately 11-17 km. Here, suggest that the thickness of the upper crust is 17 km and crust is 40 km with local magnetotelluric measurements. Additionally, the electric conductor appears in the southwest of Mogod region, we interpret that conductor play as a source of geological activity of Mogod region, and it might be the signature of a remanent fluid.